PENGARUH DANA ZAKATDANTINGKATPENDIDIKAN TERHADAP KEMISKINANDI PROVINSI ACEH - Lisnawati, Abubakar Hamzah, Nasir Azis. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2013)
Abstract:The purpose of this study to examine the effect of alms (zakat), education which are proxied by the average length of the school on poverty in Aceh province, in this case for all of districts and Cities in Aceh province in 2005-2008. Type data analyse of this study are panel data from 2008 until 2011 for time series data and cross section data represent of 23 districts in Aceh Province. So all totaled 92 Observation.methodof analysis used in this research is a method of linear regression analysis of panel data with FEM (Fixed Effect Model). The results of this study indicate that the alms (zakat) variable is negative and significant effect on poverty level. educational variables alms(zakat), while the education variables which are proxied by the average length of the school and a significant negative effect on the level of poverty in the province of Aceh. Keywords : Poverty, alms,level of education. Abstrak: Tujuan penelitian ini untuk menguji pengaruh dana zakat dan tingkat pendidikan yang diproxi dengan rata-rata lama sekolah terhadap kemiskinan di Kabupaten/ Kota di Provinsi Aceh. Jenis data yang digunakan dalam penelitian adalah data panel yang diwakili data dari tahun 2008 sampai dengan tahun 2011 dan data kerat lintang (cross section) sebanyak 23 data mewakili kabupaten/kota di Provinsi Acehsehingga menghasilkan 92 Observasi.Metode pengolahan data dengan Fixed Effect Model dan hasil penelitian menunjukkan bahwa variabel dana zakat berpengaruh negatif namun tetapi tidak signifikan terhadap kemiskinan, sedangkan variabel pendidikan yang diproksi dengan angka rata-rata lama sekolah berpengaruh negatif dan signifikan terhadap tingkat kemiskinan di Provinsi Aceh. Kata kunci: Kemiskinan, dana zakat dan tingkat pendidikan.